2006
DOI: 10.1128/mcb.00087-06
|View full text |Cite
|
Sign up to set email alerts
|

3BP2 Deficiency Impairs the Response of B Cells, but Not T Cells, to Antigen Receptor Ligation

Abstract: The adapter protein 3BP2 is expressed in lymphocytes; binds to Syk/ZAP-70, Vav, and phospholipase C-␥ (PLC-␥); and is thought to be important for interleukin-2 gene transcription in T cells. To define the role of 3BP2 in lymphocyte development and function, we generated 3BP2-deficient mice. T-cell development, proliferation, cytokine secretion, and signaling in response to T-cell receptor (TCR) ligation were all normal in 3BP2 ؊/؊ mice. 3BP2 ؊/؊ mice had increased accumulation of pre-B cells in the bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 64 publications
5
70
0
Order By: Relevance
“…Osteoclasts from DAP12 ϫ FcR␥-null mice exhibit defectiveNFATc1expressionasaconsequenceofimpairedPLC␥-dependent calcium signaling (6). Of note, B cells from 3BP2 Ϫ/Ϫ mice show impaired PLC␥ phosphorylation, calcium mobilization, and NFAT activation (24). Our observations that in myeloid cells 3BP2 forms a signaling complex with c-Src, Syk, Vav, and Cbl provide a mechanistic explanation of how 3BP2 might participate in RANK-mediated osteoclast formation.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Osteoclasts from DAP12 ϫ FcR␥-null mice exhibit defectiveNFATc1expressionasaconsequenceofimpairedPLC␥-dependent calcium signaling (6). Of note, B cells from 3BP2 Ϫ/Ϫ mice show impaired PLC␥ phosphorylation, calcium mobilization, and NFAT activation (24). Our observations that in myeloid cells 3BP2 forms a signaling complex with c-Src, Syk, Vav, and Cbl provide a mechanistic explanation of how 3BP2 might participate in RANK-mediated osteoclast formation.…”
Section: Discussionmentioning
confidence: 68%
“…Consistently, 3BP2 was found to positively regulate the activity of NFAT in T and B cells (21,23). In addition, studies in mouse deficient for 3BP2 expression have shown that 3BP2 regulates B cell development and BCR-mediated B cell activation and calcium mobilization (24,25). Finally, genetic evidence linking 3BP2 to the human genetic bone disease cherubism (31,32) indicates that 3BP2 also plays a crucial role during inflammation and bone remodeling.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Anti-PLC-␥2, anti-CD19, anti-Vav1, and anti-BLNK antibodies were from Santa Cruz Biotechnology (Santa Cruz, CA). Polyclonal anti-3BP2 antibody raised against an amino acid sequence from Leu 359 to Ser 462 of 3BP2, which is capable for the immunoprecipitation of 3BP2, was a gift from Dr. Raif S. Geha (Harvard Medical School) (32). Anti-glutathione S-transferase (GST) mAb was from Nacalai (Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Suppression of the 3BP2 expression by small interfering RNA results in the inhibition of BCR and T cell receptor (TCR)-mediated activation of NFAT (25,31). Analysis of 3BP2-deficient mice demonstrated that 3BP2 is required for B cell proliferation and cell cycle progression (32,33). Lack of 3BP2 results in the abnormal phenotype in splenic marginal-zone B cells and peritoneal B1 B cells and diminished thymus-independent type 2 antigen response (33).…”
mentioning
confidence: 99%